2017
DOI: 10.3390/ijms18102079
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of Epithelial-to-Mesenchymal Transition in Prostate Cancer Progression

Abstract: In prostate cancer (PCa), similar to many other cancers, distant organ metastasis symbolizes the beginning of the end disease, which eventually leads to cancer death. Many mechanisms have been identified in this process that can be rationalized into targeted therapy. Among them, epithelial-to-mesenchymal transition (EMT) is originally characterized as a critical step for cell trans-differentiation during embryo development and now recognized in promoting cancer cells invasiveness because of high mobility and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 148 publications
2
75
0
1
Order By: Relevance
“…Snail, Slug, Twist1, ZEB1, and ZEB2 are transcriptional regulators of EMT which regulates the expression of E‐Cadherin, Vimentin, and N‐cadherin. Snail and Slug are zinc finger transcription factors that belong to SNAI family which are dominant regulators of EMT in many cancers including PCa (Ganesan, Mallets, & Gomez‐Cambronero, ; Lo, Lee, Lee, & Hsieh, ). Results from this study revealed that overexpression of the VCP is associated with upregulation of Snail and Slug transcription factors and elevated Vimentin and decreased E‐cadherin expression correlating to EMT of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snail, Slug, Twist1, ZEB1, and ZEB2 are transcriptional regulators of EMT which regulates the expression of E‐Cadherin, Vimentin, and N‐cadherin. Snail and Slug are zinc finger transcription factors that belong to SNAI family which are dominant regulators of EMT in many cancers including PCa (Ganesan, Mallets, & Gomez‐Cambronero, ; Lo, Lee, Lee, & Hsieh, ). Results from this study revealed that overexpression of the VCP is associated with upregulation of Snail and Slug transcription factors and elevated Vimentin and decreased E‐cadherin expression correlating to EMT of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cadherin, Vimentin, and N-cadherin. Snail and Slug are zinc finger transcription factors that belong to SNAI family which are dominant regulators of EMT in many cancers including PCa(Ganesan, Mallets, & Gomez-Cambronero, 2016;Lo, Lee, Lee, & Hsieh, 2017).…”
mentioning
confidence: 99%
“…Increasing evidences suggest that EMT plays a role in the regulation of PCSCs, metastatic ability and therapy resistance of PCa cells, reviewed in [101]. A number of different factors might contribute to EMT in PCa including autocrine and paracrine signaling molecules released by tumor cells and stroma, for example, transforming growth factor beta 1 (TGF-β1), fibroblast growth factor (FGF), interleukin 6 (IL-6), hypoxia-inducible factor (HIF), and Wnt ligands as reviewed previously [102]. EMT can also be triggered by anticancer therapy including ADT, chemotherapy, and radiotherapy.…”
Section: Epithelial-mesenchymal Transition and Pcscsmentioning
confidence: 99%
“…It is a complex mechanism which involves modification of various signaling pathways. These pathways are regulated by several transcriptional factors, notably SNAIL, Zinc finger protein SNAI2(SLUG), TWIST 1/2 , ZEB 1/2 [118]. In PCa, miRNAs have been shown to induce EMT by regulating these transcription factors directly [119,120].…”
Section: Mirna During the Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%